Intensive blood pressure control in isolated systolic hypertension: a post hoc analysis of a cluster randomized trialResearch in context - Chang Wang; Songyue Liu; Wei Miao; Ning Ye; Ziyi Xie; Lixia Qiao; Nanxiang Ouyang; Yangzhi Yin; Yingxian Sun; Guozhe Sun (Elsevier, 2024)
Summary: Background: The isolated systolic hypertension (ISH) is of high prevalence, with a relatively poor prognosis. However, there is still no direct evidence to demonstrate the benefits of intensive blood pressure (BP) control among these patients. We aimed to evaluate intensive BP control with the target of <130/80 mmHg in ISH. Methods: This was a post hoc analysis of patients with ISH in the China Rural Hypertension Control Project (CRHCP), defined as systolic blood pressure (SBP) ≥ 140 mmHg and diastolic blood pressure (DBP) < 90 mmHg. The primary outcome was cardiovascular disease (CVD) including stroke, myocardial infarction, heart failure, and CVD death. Mixed-effect Cox proportional regression and generalized estimating equation models were used for analysis. Findings: In total, 7981 patients were randomly assigned to the intervention group and 8005 to the usual care group between May 8 and November 27, 2018. The median follow-up was 3.02 years (25-75%: 2.98-3.06). Mean systolic/diastolic BP at the end of 36 months follow-up was 126.5/71.2 mmHg in the intensive BP control group and 148.1/78.6 mmHg in the usual care group. The intervention group presented a substantially lower rate of composite CVD compared with the usual care group (1.52% versus 2.30%/year; multiple-adjusted hazard ratio (HR): 0.64; 95% confidence interval (CI): 0.57-0.72; P < 0.001), especially for stroke (multiple-adjusted HR: 0.61; 95% CI: 0.53-0.70; P < 0.001), HF (multiple-adjusted HR: 0.57; 95% CI: 0.36-0.91; P = 0.017) and CVD death (multiple-adjusted HR: 0.64; 95% CI: 0.50-0.83; P < 0.001). The primary composite outcome was substantially reduced by 36% in the intervention group compared with the usual care group. The further interaction analysis revealed that the reduction of primary outcome by intervention was consistent across subgroups of sex, age, education level, history of CVD, use of antihypertensive medication and baseline DBP (P > 0.05 for all interaction test). The incidences of symptomatic hypotension, syncope injurious falls and renal outcomes did not differ between the two groups, even though hypotension was increased in intervention group (RR:1.71; 95% CI: 1.28-2.28; P < 0.001). Interpretation: Intensive BP control (<130/80 mmHg) was effective and safe in patients with ISH for the prevention of CVD events. Funding: The Ministry of Science and Technology (China) of China and the Science and Technology Program of Liaoning Province, China.